Mission-Oriented Innovation Policy: E-Government Development Trajectory in Indonesia's Bureaucratic Reform - Manjali, Regina (Universitas Airlangga, 2023)
The complex and evaluative nature of bureaucracy in Indonesia has posed significant challenges in its implementation. In response, the Indonesian government has prioritized the digitalization of government administration through the adoption of the e-government system. This paper investigates the trajectory of the e-government system in Indonesia, with a specific focus on Sistem Pemerintah Berbasis Elektronik (SPBE) as a pivotal element of the mission-oriented innovation policy. Through a thorough literature analysis, this study emphasizes the importance of embracing a mission-oriented strategy to effectively address governance issues and foster innovation. Additionally, it explores the roles of key actors involved in the policy process and examines the diverse factors that influence policy outcomes. The findings highlight the instrumental role of the maturity index in policy implementation and its impact on achieving policy objectives. Furthermore, this paper discusses the various challenges and opportunities arising in the context of e-government implementation in Indonesia.Keywords: Mission-Oriented, Innovation Policy, E-Government, Bureaucratic Reform